The effect of pH on oocyte ratio for Paracheirodon axelrodi kept in captivity (Orinoquia, 2014)
Paracheirodon axelrodi (cardinal tetra) is the most commercialised and exported ornamental fish species in Colombia. The fishes that are to be sold are taken from the environment there by affecting populations; this has led to studying their reproductive biology for developing protocols regarding reproduction in captivity. The present study evaluated the effect of two ranges of pH in water during a six-month period (T1: 5.5 - 5.8 and T2: 7.0 - 7.5) regarding adult femaleP. axelrodi growth and oocyte rate at histological level for establishing whether this would affect gonad development and growth. The results showed that pH ranges did not affect the percentage of early and late perinucleolus stage, cortical-alveoli, vitelogenic oocytes, nor oocytes developing atresia; however, the conditions so maintained favoured variables regarding growth. Oocyte ratios were kept similar during experimentation time; late vitelogenesis oocytes had the second greatest cell ratio from the start to the end of the experiment. This result led to conclude that the conditions to which P. axelrodi were submitted allowed females to be kept in a state of advanced maturity for six months, and if the parameters triggering females' final maturation and spawning were established, then mature individuals could be had for a prolonged period.Key words: Environment; captivity; physicochemical; histology; maturation; oocyte.
Keywords: Environment; captivity; physicochemical; histology; maturation; oocyte